Evaluation of surface roughness and varnish bonding strength of wood subjected to different sandpaper and sanding orientation - Lee, Kian Yang (Nanyang Technological University, 2021)
As wood are commonly used in manufacturing and furniture making, processing of wood typically includes sanding and applying of varnish for decorative or durability purposes. The objective of this final year project is to determine the effects of surface roughness and varnish bonding strength subjected to different sandpaper and sanding orientation on wood that are popular within Singapore, namely Chengal and Nyatoh. The method used to quantify the surface roughness will be a stylus profilometer and Ra, Rz and Rq values will be discussed. For varnish bonding strength, a Shimadzu universal testing machine will be employed to quantify the tensile force required to remove the varnish from the wood surface through conducting a tensile pull-out test with a metal dolly that is glued to the varnished wood. Surface roughness analysis was conducted with Mitutoyo Surftest SJ-301. For Chengal, highest and lowest surface roughness values were found using 80-grit sandpaper when sanded against grains and grit-220 sandpaper when sanded along grains, respectively. For Nyatoh, highest and lowest surface roughness values were found using 80-grit sandpaper when sanded along grains and grit-220 sandpaper when sanded along grains, respectively. A general trend of decreasing surface roughness of all roughness parameters can be observed when sanded with increasing grits of sandpaper. For Chengal, sanding along grains achieved lower surface roughness as compared to sanding against grains for all 3 sandpaper grit size used in this experiment. However, Nyatoh did not conform to such trend. For the varnish bonding strength, Chengal that was sanded with 80-grit sandpaper against grains had the highest varnish bonding strength of 3.666 MPa. Nyatoh that was sanded with 220-grit sandpaper along grains had the highest varnish bonding strength with a value of 5.705 MPa. No distinct trends can be observed for Chengal on the relationship between varnish bonding strength and surface roughness as well as varnish bonding strength and sanding orientation. No further analysis was done for Nyatoh as the varnish bonding strength analysis may be inaccurate due to the wood fibres being pulled out together with the varnish.